Functional Existence of Samadi an Ethnic Socio-Cultural Establishment of the Tiwas in North East India - Jitumoni Bordoloi, Ajit Sarmah, Ranjit Bordoloi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
North-Eastern part of India represent by numerous social groups having its own history, culture, beliefs, customs and tradition. There have been many linguistic waves of migrations came about across numerous points over time to the current region. The Lalung (Tiwa) are one of the earliest groups migrating from Tibet and like better to quiet down central Assam i.e. some villages in Jorhat, Lakhimpur and Dhemaji district of province and Ri-bhoi district of Meghalaya. Linguistically they additionally belong to the Sino-Tibetan group. Dormitory (Samadi) a roof covering bamboo floor with a beautifully decorated by Thum-thuna massive spherical post and wooden entrance steps while not wall is a traditional centre for culture learning academy village port wherever the youth like to be a part of the establishments for dance and entertains, sleep and rest, training for handicrafts, discussion cum security and protection measure of the life of the villagers with open minded for brotherhood and corporation among the members. It’s additionally a ritual centre and as Vaisnavism spread in plains its importance functional and existence of Samadi as a standard ethnic democratic establishment decreased. Limitation and objective of this article is to review regarding the normal youth dormitory (Samadi) its functional existence in the Tiwa society. Field visit, interview and numerous observations from hills and plains areas of Assam is taking for thought for study into consideration in the piece of article.